PREPARATION AND STRUCTURE OF CH2CH2OOCCHCH2SNCL3 - JUNG, OS; LEE, YA; JEONG, JH; SOHN, YS (KOREAN CHEMICAL SOC, 1992)
A new estertin, CH2CH2OOCCHCH2SnCl3, was prepared and its structure was determined by X-ray crystallography (P2(1)2(1)2(1); a=9.439(1), b=9.601(1), c=10.779(1) angstrom, Z=4) and refined to R=0.0356. The coordination geometry around the tin atom approximates to a trigonal bipyramid with the intramolecularly coordinated oxygen 0(1), (Sn-O(1), 2.482(6) angstrom) and Cl(2) occupying mutually trans positions (0(1)-Sn-Cl((2), 176.4(2)-degrees).
Keywords: CRYSTAL-STRUCTURE; CHEMISTRY; TIN